ТУННЕЛЬ ДИОДЛАРИДА ҲОСИЛ БЎЛУВЧИ ОРТИҚЧА ТОКНИНГ ТУРЛИ МОДЕЛЛАРДАГИ КЎРИНИШИ - Гулямов, Г.; Дадамирзаев, М.Ғ.; Ўктамова, М.К. (SCIENCE and SOCIETY, 2022)
In this paper, the excess current generated in the tunnel diode was analyzed with the Chynowez model, based on the theory of Knott and Demass. Based on the Franz-Keldesh model for various values of the electric field, the current-voltage characteristic of the tunnel diode was obtained from the change in the excess current of the tunnel diode.